PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING: (Studi Kasus pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang terdaftar di BEI periode 2013-2017) - Ayu Anggraini (Jurnal Statistika Industri dan Komputasi, 2019)
This study aims to analyze profitability, firm size and growth opportunity which affect the comanies value with capital structure as an intervening variable on food and baverage manufacturers companies go public listed on the BEI. The population used is food and baverage manufacturing companies. By purposive method of company data which is used as research sample as 10 companies listing in BEI period 2013-2017. Data management is done by multiple regression method to show how independent variable influence dependent variable. This study finds that (1) profitability has positive influence on capital structure, with a significance value 0,003. (2) firm size has positive influence on capital structure with a significance value 0,042. (3) growth oppotuniry has negative influence on capital structure, with a significance value 0,191. (4) capital structure has negative influence on firm size with a significance value 0,105. (5) profitability has negative influence on firm size with a significance value 0,566.(6) firm size has negative significant influence on firm size with a significance value 0,004. (7) growth opportunity has negative influence on firm size with a significance value 0,719. Profitability and firm size have indirect effect on firm value with capital structure as an intervening variable, while growth opportunity have indirect effect on firm value.